Promotion of international sport initiatives by local governments: A quantitative text analysis of the local sport promotion plans - Kubota, J.; Waku, T. (Japan Journal of Physical Education, Health and Sport Sciences, 2023)
The purpose of this study was to examine the development of the Local Sport Promotion Plans (hereafter, the Plans) and the promotion of international efforts through sport by the local governments in Japan by summarizing the status of development and the characteristics of international efforts for the Plans. The Plans included in FY2022 publicly available on the websites of local governments were organized into categories. Sentences containing words related to international efforts were then extracted from these plans and subjected to quantitative text analysis using KH Coder 3. This revealed that approximately 30% of local governments had developed such Plans, and that the percentage of local governments with the Plans tended to drop as the population size decreased. This suggests it is important to encourage local governments with smaller populations to develop the Plans under leadership at the prefectural level and enhance the development of administrators and information provision for those playing a central role in policy making. Similarly, it was found that the number of sentences and texts related to international efforts in the Plans was reduced as the population size decreased. This may have been due to differences in human and economic resources among the local governments. In order for local governments with smaller populations to bring about positive changes in their communities through international sport initiatives, it will be important for prefectures and local governments with larger populations to develop and operate systems, mechanisms, and structures that enable local governments with smaller populations to get involved and work together. It was also recognized that many international sport initiatives in the Plans often mentioned the promotion of "efforts and support for strengthening athletes" and "regional revitalization through interaction with athletes and attracting pre-training camps associated with sporting events". In the light of the current National Sport Basic Plan and the International Strategy for Sport, strategic bidding and hosting of international sporting events and the creation of various ripple effects within communities by leveraging these opportunities are important measures for Japan's national sport policy. One possible measure for addressing the 2 major interests in the Plans presented in this study would be to create and utilize the various opportunities associated with strategic bidding and hosting of international sporting events, and would help to promote positive effects and control negative effects.